THE EFFECT OF GREEN MARKETING MIX ON THE BRAND IMAGE OF TEA BOX ULTRA JAYA (STUDY ON STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS UNIVERSITY MUHAMMADIYAH NORTH SUMATRA) - Satria Tirtayasa; Anita Mura Islaini; Tohap Parulian; Hery Syahrial (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The purpose of the authors of this research is to determine and analyze the effect of the Green Marketing Mix on the Ultrajaya Box Tea Brand Image in Students of the Faculty of Economics and Business, Muhammadyah University, North Sumatra. The benefits of this research are to improve and broaden knowledge, especially about Green Marketing. In determining the sample, the researcher used the Slovin formula in order to obtain a total of 96 students. The data analysis technique in this study used a quantitative and associative approach. Based on the results of this study, it shows that the regression values that have the greatest influence is the value of the Promotion variable (X4) of 50.3%. The results of the t test on the product (X1) on the brand image obtained shows that the product (X1) has a positive and significant effect on brand image,the results of the effect of Price (X2) on Brand Image revealed that the Price (X2) has a positive and significant effect on Brand Image. Meanwhile,  the test results of the impact of Distribution Channels (X3) on Brand Image shows that Distribution Channel ( X3) has a positive and significant influence on Brand Image. Furthermore,the results of the impact of  Promotion (X4) on the Brand Image shows that Promotion (X4) has a positive and significant effect on Brand Image (Y). The results of the F test on the Effect of Green Marketing Mix on Brand Image found that simultaneously between Products, Prices, Distribution Channels and Promotion have a significant influence on Brand Image. And based on the results shown by R-Square is 0.555 or 55.5%, which means that about 55.5% of the Brand Image variable (Y) and can be explained by the Product (X1), Price (X2), Distribution Channel (X3 ) variables. and Promotion (X4) and the remaining 44.5% is used as influence by other variables that are not studied.